Heavy metal (loid)s phytotoxicity in crops and its mitigation through seed priming technology. Issue 2 (28th January 2023) - Singhal, Rajesh Kumar; Kumar, Mahesh; Bose, Bandana; Mondal, Sananda; Srivastava, Sudhakar; Dhankher, Om Parkash; Tripathi, Rudra Deo
Abstract: Unexpected bioaccumulation and biomagnification of heavy metal(loid)s (HMs) in the environment have become a predicament for all living organisms, including plants. The presence of these HMs in the plant system raised the level of reactive oxygen species (ROS) and remodeled several vital cellular biomolecules. These lead to several morphological, physiological, metabolic, and molecular aberrations in plants ranging from chlorosis of leaves to the lipid peroxidation of membranes, and degradation of proteins and nucleic acid including the modulation of the enzymatic system, which ultimately affects the plant growth and productivity. Plants are equipped with several mechanisms to counteract the HMs toxicity. Among them, seed priming (SP) technology has been widely tested with the use of several inorganic chemicals, plant growth regulators (PGRs), gasotransmitters, nanoparticles, living organisms, and plant leaf extracts. The use of these compounds has the potential to alleviate the HMs toxicity through the strengthening of the antioxidant defense system, generation of low molecular weight metallothionein's (MTs), and phytochelatins (PCs), and improving seedling vigor during early growth stages. This review presents an account of the sources, uptake and transport, and phytotoxic effects of HMs with special attention to different mechanism/s, occurring to mitigate the HMs toxicity in plants employing SP technology. Novelty statement: To the best of our knowledge, this review has delineated the consequences of HMs on the crucial plant processes, which ultimately affect plant growth and development. This review also compiled the up to dated information on phytotoxicity of HMs through the use of SP technology, this review discussed how different types of SP approaches help in diminishing the concentration HMs in plant systems. Also, we depicted mechanisms, represent how HMs transport and their actions on cellular levels, and emphasized, how diverse SP technology effectiveness in the mitigation of plants' phytotoxicity in unique ways.